New criteria for the determination of the parallel-to-grain embedment strength of wood. (10th June 2018) - Yurrita, Miguel; Cabrero, José Manuel
Highlights: Embedment strength is a main parameter in the dowel-type timber connections analysis. The work proposes to consider it as a system instead of a material property. A new formula is presented, with a non-linear relation with timber density. Dowel diameter is discarded as a primary factor. The influence of steel properties on the embedment strength should be considered. Abstract: The calculation of the capacity of structural timber connections with dowel-type-fasteners requires the embedment strength of timber, which relies on expressions based on experimental tests. Most of the existing formulae were fitted for softwoods. However, in the case of hardwoods, which are being increasingly used in construction, their embedment strength is considerably underestimated. Herein, a different approach for the determination of the embedment strength is presented, compared against existing models, calibrated and validated with an extensive experimental data set of embedment tests. The study concludes that the consideration of the dowel diameter as a main factor in the parallel-to-grain direction case should be rejected. Instead, dowel material properties (here the hardness is proposed) have to be introduced as a main factor.